Presence of env-like sequences in Quercus suber retrotransposons - Carvalho, M.; Ribeiro, T.; Viegas, W.; Morais-Cecílio, L.; Rocheta, M. (Journal of Applied Genetics, 2010)
The main difference between LTR retrotransposons and retroviruses is the presence of theenvelope (env) gene in the latter, downstream of thepol gene. Theenv gene is involved in their infectious capacity. Here we report the presence ofenv-like sequences in the genome ofQuercus suber (cork oak), one of the most economically important Portuguese species. These gene sequences were isolated through DNA amplification betweenRNaseH conserved motifs and 3’ LTR, based on the structure ofcopia retrotransposons. Phylogenetic analysis revealed that almost all the clones isolated are clustered withCyclops-2, aTy3-gypsy element identified inPisum sativum, except one clustered withgypsy andcopia retroelements found in different species. This suggests the existence of a potential ancestral sequence of theenv gene, prior to the separation ofTy3-gypsy andTy1-copia retrotransposons. Additionally, the isolatedenv-like sequences showed 26–39% of homology withenv-like sequences characterized in viruses. The origin ofenv-like sequences in retrotransposons from host plant taxa is discussed.
The following values have no corresponding Zotero field: publisher: Springer-Verlag
Keywords: copia retroelements; Cork oak; envelope-like gene; retrotransposons; retrovirus